The Effects of Transformational Leadership, Competence, and Compensation On Employee Performance: The Mediating Role of Self-Efficacy - Melynda, Margaretta Ineke; Trisninawati (JENIUS (Jurnal Ilmiah Manajemen Sumber Daya Manusia), 2026)
Employee performance is an important factor in improving hospital service quality. Organizational factors such as transformational leadership, competence, and compensation are believed to influence employee performance. In addition, self-efficacy, defined as employees’ belief in their abilities, is considered an important mediating variable. This study aimed to analyze the effect of transformational leadership, competence, and compensation on employee performance through self-efficacy at RSUD Dr. H. Mohamad Rabain Muara Enim. This quantitative descriptive study involved 271 employees selected using stratified random sampling. Data were collected through questionnaires distributed via Google Forms and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that transformational leadership positively affected employee performance (β=0.078; T=1.975; P=0.001), as did competence (β=0.295; T=4.698; P=0.000). Compensation had no significant direct effect on performance (β=-0.05; P=0.052). Transformational leadership (β=0.162; P=0.000), competence (β=0.295; P=0.000), and compensation (β=0.112; P=0.001) significantly influenced self-efficacy. Self-efficacy also significantly affected employee performance (β=0.630; T=10.404; P=0.000). Furthermore, self-efficacy mediated the effects of transformational leadership (β=0.102; P=0.035), competence (β=0.439; P=0.000), and compensation (β=0.071; P=0.002) on employee performance. These results indicate that improving employee performance depends not only on organizational factors, but also on individual confidence in their ability to carry out tasks. This research is expected to provide theoretical contributions to the development of human resource management, especially in healthcare organizations, as well as become a practical consideration for hospital management in formulating policies to improve employee performance sustainably.